Weed dynamics in grain sorghum-grass intercropped systems - Sodré Filho, Joilson (2014)
The aim of this study was to assess the influence of short-season sorghum-grass intercropped systems on weed population dynamics. The integrated systems consisted of sorghum grown at two row spacings (0.50 m and 0.70 m), intercropped with palisade grass or Congo grass. We also used sole crops of sorghum, palisade grass, Congo grass and a fallow to serve as a reference for spontaneous vegetation. The experiment was conducted in 2010 and 2011 at Planaltina (Federal District) in Brazil. Weed populations and weed dry matter were assessed during the short season and during the succession soybean cycle. The weed soil seed bank was sampled in both years of the study. Sorghum at a row spacing of 0.50 m intercropped with Congo grass reduced the Ageratum conyzoides population. The Tridax procumbens seed bank in the soil was reduced by using sorghum at a the row spacing of 0.70 m, whether intercropped or not. Planting palisade grass during the short season reduced Digitaria sanguinalis in the soil seed bank. Planting palisade grass or Congo grass as a sole crop or intercropped reduced the number of weed seeds in the soil, showing that these species can be recommended for integrated weed management in intercropped systems.